Efficacy and safety of docetaxel plus S-1-based therapy in gastric cancer: a quantitative evidence synthesis of randomized controlled trials - Lv, Hui-Fen; Qin, Li-Feng; Ran, Rui-Zhi; Jiang, Xue-Ping; Zhao, Fang-Yu; Li, Bo (Frontiers in Pharmacology, 2024)
Objective: To systematically evaluate the safety and efficacy of docetaxel plus S-1-based therapy in gastric cancer treatment. Methods: PubMed, Embase, The Cochrane Library, and Web of Science electronic databases were searched for randomized controlled trials on docetaxel plus S-1-based therapy in the treatment of gastric cancer from the establishment of the database to September 1, 2022. Relevant studies were included per pre-defined eligibility criteria, and two researchers independently screened and assessed the included literature using Review Manager v5. Outcome measures and statistics related with efficacy and safety profiles were extracted from the included studies, and Stata v15.1 was used for pooled analysis. Results: Objective response rate (OR = 2.34, 95%CI = [1.32, 4.13], P = 0.003), relapse-free survival (HR = 0.68, 95%CI = [0.58, 0.79], P < 0.001), progression-free survival (HR = 0.81, 95%CI = [0.68, 0.96], P = 0.016) and overall survival (HR = 0.86, 95%CI = [0.79, 0.95], P = 0.002) of docetaxel plus S-1-based therapy (DS-based therapy) in gastric cancer treatment were better than the non-DS-based therapy. However, DS-based therapy was associated with increases risk of certain adverse drug effects, such as alopecia, leukopenia, and oral mucositis. Further studies are warranted to validate the efficacy superiority of DS-based versus non-DS-based regimens, per our trial sequential analysis findings. Conclusions: DS-based therapy significantly improves patients’ clinical outcome in gastric cancer, albeit at the cost of increased toxicity. Further RCTs are needed to confirm the efficacy superiority of DS-based regimens.